2021
DOI: 10.1080/21655979.2021.1997366
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and structural characteristics of soil microbial communities in different habitats of wild Lilium regale Wilson in Wenchuan area

Abstract: Lilium regale Wilson ( L.regale ), originated in the Minjiang River basin in Sichuan, China, has different phenotypic characteristics in different environments. To analyze the correlation between the phenotypes of L.regale and its soil micro-ecological environment, wild habitat soil of L.regale at the two altitudes were selected to analyze the diversity and community structure of microorganisms in soil, and measure the soil physico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In Z. mays , ZmCCoAOMT2 and ZmCAD , which are involved in lignin biosynthesis, were confirmed to encode components of the QTR mechanism protecting against leaf diseases [ 28 , 29 ]. As a highly resistant wild lily, L. regale is valuable for breeding disease-resistant lily varieties [ 30 ]. Although previous research has identified several WRKY TFs that positively regulate L. regale resistance to fusarium wilt, the QTR mechanism has not been thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In Z. mays , ZmCCoAOMT2 and ZmCAD , which are involved in lignin biosynthesis, were confirmed to encode components of the QTR mechanism protecting against leaf diseases [ 28 , 29 ]. As a highly resistant wild lily, L. regale is valuable for breeding disease-resistant lily varieties [ 30 ]. Although previous research has identified several WRKY TFs that positively regulate L. regale resistance to fusarium wilt, the QTR mechanism has not been thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Soil samples were collected from 12 areas within the range of wild F. przewalskii between late July and early August, including Weiyuan County (WY), Linxia County (LX), Diebu County (DB), Ruoergai County (RG), Ganzi Tibetan Autonomous Prefecture (GZ), Shiqu County (SQ), Luhuo County (LH), Zeku County (ZK), Yushu City (YS), Zaduo County (ZD), Maqin County (MQ), and Ledu District (LD) (Figure 1). At each site, five F. przewalskii plants were randomly selected by five-point sampling method (Xie et al, 2021). We only chose plants that had grown for more than 3 years.…”
Section: Soil Collectionmentioning
confidence: 99%
“…We found that the specific distribution at the genus level was a major factor contributing to the differences of rhizosphere bacterial communities among sites (Figure 6A). When the relative abundance greater than 1% in each sample, we classified the common genera (Xie et al, 2021). In total, there were 9 common genera: Gp4 (2.57-12.59%), Spartobacteria (1.02-6.46%), Pseudomonas (1.08-5.27%), Gp6 (1.70-5.89%), Aridibacter (1.02-4.37%), Chryseolinea (1.12-3.98%), Saccharibacteria (1.23-3.08%), Nitrospira (1.23-3.39%), and Terrimonas (1.07-2.69%) (Figure 6B).…”
Section: Soil Bacterial Community Compositionmentioning
confidence: 99%
See 1 more Smart Citation